Dilatancy signatures of amorphous plasticity probed by X-ray synchrotron radiation. (April 2019) - Sun, X.; Ding, G.; Mo, G.; Dai, L.H.; Jiang, M.Q.
Abstract: The dilatancy signatures associated with the plastic deformation of a typical Zr-based amorphous alloy are captured by using synchrotron radiation X-ray diffraction (XRD) and small angle X-ray scattering (SAXS) techniques. XRD demonstrates that the right-subpeak atoms of the second coordination shell accommodate the local dilatation, which occurs prior to the plastic yielding and during the softening-to-flow transition process. Mediated by the local dilatation, local atomic rearrangements can operate at the left-subpeak of the second shell and/or at the fourth shell with a characteristic lengthscale of about 1 nm. The obtained dilatancy signatures of amorphous plasticity are further confirmed by SAXS in terms of the nano-scale structural heterogeneity. Graphical abstract: Image 1 Highlights: Dilatancy of amorphous plasticity is probed by X-ray synchrotron radiation. Right-subpeak atoms of the second coordination shell accommodate local dilatation. Local atomic rearrangements can operate at a lengthscale up to 1 nm. Nanoscale atomic rearrangements are activated by subnano-scale dilatation.